NEUROPSYCHOLOGICAL BASIS OF THE PROBLEM OF DEVELOPMENT OF MOTOR AREAS AND ITS DISORDERS (Conference Zone, 2022)
This article presents an analysis of the pedagogical and psychological literature of motor areas on the neuropsychological aspects of motor development in children and its problems.